Cultural Reproduction of the Jawi Book in the Recitation Tradition in Palembang - Bety Bety; Ris'an Rusli; Choirunniswah Choirunniswah; Mohammad Syawaluddin; Maryam Maryam (UIN Sunan Gunung Djati, 2023)
The Jawi Books, an essential component of Islamic teachings in Southeast Asia, plays a vital role in cultural and religious education. Its study in Palembang, Indonesia, provides insights into the processes of cultural reproduction and adaptation within a contemporary context. This qualitative research explores the teaching methods, motivations, and cultural implications associated with studying the Jawi Books in Palembang. The methodology includes interviews with local scholars, observations of teaching sessions, and an analysis of the content and usage of the Jawi Book in various religious assemblies. The research discovered that the primary motivation for studying the Jawi Books is to aid local congregations in understanding Arabic texts. Despite its historical roots, the Jawi Books remains a significant source of religious knowledge, supported by a strong network of scholars across regions such as Kalimantan, Aceh, Malaysia, and Thailand. The teaching methods are varied, combining traditional approaches like the talaqqi method with modern digital platforms, including YouTube. The study uncovers a symbolic power struggle in the interpretation between Hadromaut and local Palembang clerics, suggesting widespread cultural assimilation. The study of the Jawi Books in Palembang is a prime example of cultural reproduction, adapting traditional Islamic teachings to contemporary needs and contexts, which is crucial for maintaining the relevance and transmission of religious knowledge across generations. These findings underscore the importance of local interpretations and teaching methods in preserving cultural and religious identities in an increasingly globalized world.